Juridical Analysis of a Criminal Offense Involving Sexual Intercourse with a Child - Djabar, Oktavia (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the juridical aspects of criminal offenses involving sexual intercourse with a child, particularly within the framework of Indonesian criminal law. The objective is to understand the legal foundations, application of statutory provisions, and legal consequences imposed on perpetrators. The research employs a normative juridical method with statutory and case approaches, focusing on the analysis of legal norms and court decisions to assess how these laws are implemented in practice. The findings reveal that such offenses are governed by the Indonesian Penal Code (KUHP) and Law No. 35 of 2014 on Child Protection. In practice, challenges include inconsistencies in sentencing, evidentiary barriers, and the psychological vulnerability of victims. This study underscores the need for a firmer and more consistent application of the law to ensure justice and deterrence. The novelty of this research lies in its critical examination of judicial reasoning in selected verdicts, exposing gaps and disparities in legal interpretation and sentencing. This analysis contributes to the discourse on child protection by offering legal insights that promote uniformity and fairness in handling such cases. In conclusion, the study recommends reforms in judicial practices, the implementation of child-friendly legal procedures, and stronger enforcement of sentencing guidelines to better safeguard children’s rights.